Voltage control in the stator circuit of cage induction machine operating as generator in small scale hydropower plant - Kandyba, Andrzej; Kalus, Marian; Kurytnik, Igor Piotr (Publishing House of Lviv Polytechnic National University, 2012)
The synthesis of RMS voltage control system in the stator circuit of squirrel cage induction machine based on the linear criterion of " optimum magnitude" by C. Kessler 'a was performed. The squirrel cage induction machine was operating as a generator in autonomous (isolated) network. Induction machine is driven by an induction machine supplied from the inverter, which simulates the low pressure head water turbine. Synthesis process of the control system was supported by experimental studies of this system. За лінійним критерієм модульного оптимуму (за Кесслером) синтезовано регулятор діючої напруги статора асинхронної машини з короткозамкненим ротором. Асинхронна машина з короткозамкненим ротором працює в режимі генератора в автономній мережі. Асинхронний генератор приводиться в рух асинхронним двигуном, що живиться від інвертора, для імітації гідротурбіни низького тиску. Адекватність отриманих результатів підтверджено експериментом.
Регулювання напруги в колі статора асинхронної машини з короткозамкненим ротором, що працює в режимі генератора малої гідроелектростанціі
Keywords: Small hydroelectric power plant; asynchronous generator; isolated grid; control system